2016
DOI: 10.17072/1994-9960-2016-3-168-181
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Methodological Toolkit for Assessing Energy Efficiency of an Industrial Enterprise

Abstract: В.А. Кокшаров, канд. экон. наук, доцент кафедры «Экономика транспорта» Электронный адрес: Vakoksharov@mail.ru Уральский государственный университет путей сообщения, 620034, Россия, г. Екатеринбург, ул. Колмогорова, 66 В новых условиях хозяйствования управление энергопотреблением промышленного предприятия требует совершенствования методического инструментария оценки энергоэффективности, поскольку он не позволяет комплексно оценивать процессы динамичного взаимодействия энергетического хозяйства предприятия с рын… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The energy economy of an industrial enterprise is a complex production subsystem for modeling and research, which is an integral part of the overall system of an industrial enterprise. It is characterized by the presence of a large dimension, the complexity of the existing direct and feedback links between its main elements, the irregular distribution of the consumption of fuel and energy resources over time, the presence of heterogeneous components in its composition [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy economy of an industrial enterprise is a complex production subsystem for modeling and research, which is an integral part of the overall system of an industrial enterprise. It is characterized by the presence of a large dimension, the complexity of the existing direct and feedback links between its main elements, the irregular distribution of the consumption of fuel and energy resources over time, the presence of heterogeneous components in its composition [1].…”
Section: Introductionmentioning
confidence: 99%
“…The need to take into account many factors in the study of electricity consumption processes has been shown in many studies. Thus, in [1] it is proposed to use a dynamic assessment of the efficiency of energy consumption as a certain ratio of the growth rates of energy and economic criteria for the development of an enterprise. This assessment should be formed taking into account the following indicators:  growth rate of profit from the sale of marketable products;  growth rate of sold commercial products (D);  growth rate of use of secondary energy resources;  growth rate of power consumption;  growth rate of energy supply costs;  growth rate of energy resources consumed by the enterprise;  growth rate of gross emissions of harmful substances from fuel combustion into the atmosphere of the region.…”
Section: Introductionmentioning
confidence: 99%